Analysis of Elasto-hydrodynamic Lubrication Characteristics of Journal Bearings Under Starved Lubrication - Zhao Dongxu; Ni Yanguang; Ma Zikui (Jixie chuandong)
With the gradual increasing of wind turbine power, the advantages of journal bearings in wind turbine gearboxes are gradually prominent. When the lubrication system is blocked or the oil supply is insufficient, the journal bearing will be in the starved lubrication for a long time. In order to study the starved lubrication characteristics of journal bearings, based on the Reynolds equation and Reynolds boundary conditions, considering the elastic deformation of sleeves, the calculation model of journal bearings in the starved lubrication is established. The lubrication properties of journal bearings with and without elastic deformation are compared, and the influence of elastic modulus and oil supply on journal bearing properties under the starved lubrication is analyzed. The results of analysis indicate that the minimum oil film thickness considering the elastic deformation is on both sides of the bearing bush, which is more in line with the actual situation. With the increasing of elastic modulus of sleeves, the eccentricity of journals decreases, the maximum oil film pressure increases, and the minimum oil film thickness increases. With the increasing of oil supply, the eccentricity of journals decreases gradually, the maximum oil film pressure decreases, and the minimum oil film thickness increases gradually.